A Deeper Understanding of Cultural Safety, Colonising and Seating in a Teacher Education Program: A Preliminary Study - Harrison, Ed; McKay, Peter; Spencer, Marsha; Trimble, Bernadette (The Australian Journal of Indigenous Education, 2017)
This preliminary study considers the implications of where students of Aboriginal descent sat in a teacher education classroom, its significance in relation to the space of the classroom, the importance of the place to the individual and its links to creating a climate of cultural safety in the classroom. Six students from two cohorts of varying sizes were interviewed as to why they sat where they did in the classroom and why the place where they sat remained relatively stable. The study uses quotations from the students and reflectively seeks to understand their experience in the class. Risking themselves in a university context which itself is the product of the very colonisers who created the conditions for cultural genocide through residential schools. It is tentatively concluded that where First People sit in the classroom maybe reflective of the territory to which they belong.